FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2012) - Rasmini, 10.05.52.0092; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2014)
This study aims to determine and examine whether the effect of return on assets, current ratio, debt to equity ratio, total assets turn over, and free cash flow on dividend payout ratio.In this study, the selection of the sample using purposive sampling technique and obtain in sample of 64 companies listed in Indonesia Stock Exchange. Hypothesis test used in this study using multiple linear regression analysis.The results showed that return on assets positively affect on dividend payout ratio. Debt to equity ratio has a negatively affect on dividend payout ratio. Current ratio does not affect on dividend payout ratio.Total assets turn over does not affect on dividend payout ratio and free cash flow affect on dividend payout ratio.Keywords: Return On Assets, Current Ratio, Debt to Equity Ratio, Total Assets Turn Over, Free Cash Flow, dan Dividend Payout Ratio